Comparison of accredited person and medical officer discharge decisions under the Mental Health Act of NSW: A cohort study of deliberate self-poisoning patients. (February 2022) - McGill, Katie; Spittal, Matthew J; Bryant, Jennifer; Lewin, Terry J; Whyte, Ian M; Madden, Clare; Carter, Greg
Background: The Accredited Persons Programme was introduced in 2003. The relevant Mental Health Acts (NSW) authorised reviews by appropriately credentialed non-medical health professionals as part of the process of detaining and treating a person without consent: an authority previously held by medical officers. Evaluations of the Programme are needed. Objective: To compare discharge decisions for hospital-treated deliberate self-poisoning patients made by an Accredited Person and Medical Officers. Methods: For a 10-year cohort (2003–2012) of index hospital-treated deliberate self-poisoning admissions at the Calvary Mater Newcastle, we compared Accredited Person and Medical Officer discharge decisions from the general hospital. We specifically examined discharges to the psychiatric hospital under a Mental Health Act certificate (used as an index of the Accredited Person's use of the authority under the Accredited Persons Programme) compared to any other discharge destination. Unadjusted and adjusted logistic regression models and a propensity score analysis were used to explore the relationship between clinician type and discharge destination. Results: There were 2237 index assessments (Accredited Person = 884; Medical Officer = 1443). One-quarter (27%) were referred for assessment under the Act at the psychiatric hospital, with the Accredited Person significantly more likely (32%) to require this compared to the Medical Officers (24%); Risk Difference: 8.3% (4.5 to 12.1). However, after adjusting for patient characteristics; Risk Difference: −3.0% (−5.9 to −0.1) and for propensity score, Risk Difference: −3.3% (−6.7 to 0.1), the Accredited Person and Medical Officer likelihood of discharging for an assessment under the Act was similar. Conclusions: The Accredited Person assessed more clinically complex patients than the Medical Officers. After adjusting for clinical complexity and propensity score, the likelihood of referral for involuntary psychiatric hospital care was similar for Accredited Person and Medical Officers. Our evaluation of the Accredited Person programme in the general hospital was favourable, and wider implementation and evaluation is warranted.